Pengaruh Work-life balance dan Produktivitas Kerja Terhadap Kinerja Karyawan Generasi Z PT Rumah Atsiri Indonesia Dengan Kepuasan Kerja Sebagai Variabel Intervening - Kadek Grecius Calvin Gombo; Alexander Mario Retto Djong; Kristian Faskahariyanto; Truli Nugroho (ProBank, 2025)
This study analyzes the influence of work-life balance and productivity on the performance of Generation Z employees at PT Rumah Atsiri Indonesia, with job satisfaction as a mediating variable. Data were collected using a Likert-scale questionnaire and analyzed through PLS-SEM. Results show that work-life balance significantly affects job satisfaction (t = 4.786; p = 0.000) but not performance directly (t = 0.833; p = 0.406). Productivity also significantly influences job satisfaction (t = 3.884; p = 0.000), but not performance directly (t = 1.441; p = 0.150). Job satisfaction significantly impacts performance (t = 8.886; p = 0.000) and mediates the relationship between both work-life balance and productivity with performance. These findings highlight the crucial role of job satisfaction in enhancing employee performance.